ANALISIS KIMIA DAN NILAI TAMBAH BOTOK IKAN KERING - Nur Istiqamah; Saifullah; Uray Januardy (PPPM POLTESA, 2026)
Fish botok is a processed food of the Sambas people in the form of a mixture of traditional spices such as kesum leaves, turmeric leaves, noni leaves and roasted coconut, giving it a different taste from fish botok found in other regions in Indonesia. Chemical analysis of this dried fish botok is to determine the water content, ash content, fat content, protein content and carbohydrate content contained in the botok. The results of the chemical analysis can be used to ensure that dried fish botok products in the future can meet food quality standards so as to maximize competitive opportunities in a wider market. The Hayami method is used to analyze the added value of dried fish botok. Based on the results of the analysis of the added value of the Sambas typical dried fish botok innovation, it shows that with a production output of 4 kg per process, an input of 2 kg is obtained a conversion factor of 2 kg, meaning that from 1 kg of fresh fish processed into 2 kg of dried fish botok. The output value produces Rp. 300,000 / kg derived from the conversion factor multiplied by the output price. The added value obtained is Rp. 188,000 / kg obtained from the result of subtracting the output value and input contribution minus the price of raw materials.